Pemanfaatan Promotion Mix Pada Peningkatan Brand Awareness Usaha Makmur Jaya - Liliana Dewi; Evan Huttama Handoko (BIP's JURNAL BISNIS PERSPEKTIF, 2018)
Usaha Makmur Jaya has conducted various promotional activities such as direct promotion, advertisement, and exhibition to strengthen Naturalz brand. But in fact, Usaha Makmur Jaya is experiencing low sales due to lack of brand awareness on Naturalz car perfume. Usaha Makmur Jaya needs to evaluate promotional activities that can support brand awareness at Usaha Makmur Jaya. In addition to increasing brand awareness, Usaha Makmur Jaya must strengthen their brand in the market, so consumers always make Naturalz as their primary choice for car perfume, so that in the end can increase sales of the company. The purpose of this study is to evaluate promotional activities at Usaha Makmur Jaya. This research type is qualitative with semi structured interview method with 4 informant that is consumer of business of Makmur Jaya, marketing expert, and business associate of Business Makmur Jaya and also documentation in collecting data. The results of this study indicate that the factors that can increase the brand awareness of Makmur Jaya Enterprises, strengthen the Naturalz brand, and increase sales of Makmur Jaya Enterprises is by creating the right advertisement, increasing the Reseller of Makmur Jaya Business, stabilizing the price of Naturalz, following the exhibition with automotive, and doing sales promotion activities.